QSAR Studies on Thienopyrimidines as Potential Antimicrobial Agents - Jadhav, Pranali A.; Jadhav, Pratiksha (Current Drug Therapy, 2024)
Background: Recent research has revealed promising antibacterial action for thienopyrimidines. To comprehend the underlying molecular features underlying their antibacterial potency, a thorough quantitative structure-activity relationship (QSAR) investigation is required. Objectives: In order to clarify the structural parameters for effective antibacterial activity, we conducted QSAR analyses on a variety of thienopyrimidines in this work. Methods: Through the analysis of physicochemical properties and molecular descriptors, we aimed to develop predictive models that can guide the design of novel thienopyrimidine derivatives with enhanced antimicrobial potential. Results: It was discovered through the descriptor importance analysis that specific physicochemical characteristics, including lipophilicity, electronic distribution, and steric effects, significantly influenced the antibacterial efficacy of these drugs. Conclusion: The identified molecular characteristics and descriptors can be used to guide the development of new thienopyrimidine derivatives with higher antibacterial activity.
Keywords: structure-activity relationship